Regulasi UU ITE Terhadap Media Sosial di Kalangan Pelajar SMK Bina Jaya Palembang - Ermini, Ermini; Disurya, Ramanata; Suryati, Suryati; Sardana, Layang; Husnulwati, Sri; Wahyuningsih, Sri; Syam Putra, Yanuar (Universitas PGRI Palembang, 2025)
With the increasing number of violations committed by students related to the use of technology, especially in the use of social media, it is necessary to provide an understanding of how to use social media in accordance with the Electronic Transaction Information Law (UU ITE). The Law on Electronic Information Technology provides an understanding of the scope of the following regulations: how to use social media, about defamation, about violations and sanctions that we must pay attention to and of course provide an optimal understanding of the positive and negative sides of using these technological advances. By understanding and realizing/implementing the knowledge they gain about how to use social media through the ITE Law intelligently through the field of personality education such as Religious Education and Pancasila Education, the character of students who are responsible for using social media will be formed.